HIV/AIDS and disability : an exploration of organizations' responses to HIV/AIDS as it affects people with disabilities - Rohleder, Poul Andrew (Stellenbosch : Stellenbosch University, 2008)
Thesis (DPhil (Psychology))--Stellenbosch University, 2008.